Molecular genetic investigations of the diversity and origins of Old and New World cattle population - Magee, David Andrew (Trinity College (Dublin, Ireland). Department of Genetics, 2003)
One hundred and forty-nine Bos indicus mitochondrial DNA (mtDNA) control region sequences sampled from the Indian subcontinent, the Near East and East Asia were assessed in order to investigate the domestic origins and demographic history of Bos indicus cattle. Results were compared and contrasted to previously reported Bos taurus mtDNA sequences sampled in Europe, Africa, the Near East and Japan. Phylogenetic analysis reveals substantially elevated levels of Bos indicus mtDNA diversity in populations from the Indian subcontinent, which are comparable to those estimated for Bos taurus populations of the Near East - the purported cradle of Bos taurus domestication. Phylogenetic network analysis shows that Bos indicus mtDNA haplotypes cluster around one of two numerically and topologically predominant sequence variants producing starlike patterns of diversity, which are indicative of past population expansions.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin